A family study of hydrocephalus resulting from aqueduct stenosis. Issue 4 (August 1981) - Howard, F M; Till, K; Carter, C O
Abstract : Stenosis of the aqueduct of Sylvius accounts for about one third of cases of congenital hydrocephalus. At least 32 families have been reported in which the aqueduct stenosis is inherited in an X linked fashion. In half of these families, flexed adducted thumbs were noted in some affected family members. Occasionally other male members were mentally retarded, suggesting limited expression of the gene. The problem of giving genetic advice to an isolated, clinically unremarkable, case of aqueduct stenosis remains, so a family study was undertaken based on 24 such cases seen at The Hospital for Sick Children over a 19-year period. There were 15 male and nine female index patients. The diagnosis was confirmed in all cases by air encephalogram. One boy had a radial club hand and another developed clasped thumbs secondary to spasticity. No cases had hyaloidoretinal dysplasia. The 15 boys had 18 brothers and 19 sisters, of whom one sister was similarly affected. The nine girls had 12 sibs, none of whom was affected. This study, combined with a similar study in the USA, suggests that the empirical risk of recurrence of a sporadic case of aqueduct stenosis is about 4.5%.